ELEKTRONIK PEMBELAJARAN SEMESTER (E-RPS) BERBASIS WEB FAKULTAS ILMU KOMPUTER UNIVERSITAS PASIR PENGARAIAN - Yanto, Budi; Sari, Rika Perma (Riau Journal Of Computer Science, 2019)
The teaching plan is a guideline for the learning process which is then known as the Semester Learning Plan (RPS). Objectives should be clearly formulated to be achieved by the material or material to be taught, teaching and learning activities and tools used, evaluation and reference sources in the form of reading books. In the Faculty of Computer Science in filling out the Semester Learning Plan still using a manual system using Microsoft Word. Each Lecturer must fill in the Semester Learning Plan by typing Semester Learning Plan data according to the course taken on the form already made in Microsoft Word. Therefore, it is necessary to make the application of the Computer Science Learning Plan application. The E-RPS aims to make it easier for lecturers to fill out the Semester Learning Plan. The results of this practical work in the form of a website-based application that can facilitate the lecturer in filling out the Semester Learning Plan and with the lecturer no longer need to explain the contents of the Semester Learning Plan to students, because each student can see or print their own results according to the course what our want